Dynamic measurements on a Kaplan turbine: model – prototype comparison. Issue 2 (March 2019) - Angulo, M; Lucino, C; Botero, F; Rivetti, A; Liscia, S
Abstract: The purpose of this paper is to validate in prototype, the results related to the description of dynamic behaviour obtained in a Kaplan turbine model. A comparative analysis between model and prototype measurement at homologous operation conditions is presented. The phenomena of interest are tip vortex cavitation development and rotor stator interaction (rsi), associated to operation at high power outputs. The selection of suitable signal processing tools allows a clear identification of the role played by the modulation of the main rsi frequencies on cavitation phenomena. The comparison between pressure acceleration measurements on model and prototype at draft tube wall are consistent, both in time and frequency domain analysis. The acceleration measurement at the draft tube wall (manhole) is suggested as a trustworthy dynamic indicator for prediction (model) and monitoring (prototype) purposes.